Back-Splicing Transcript Isoforms (Circular RNAs) Affect Biologically Relevant Pathways and Offer an Additional Layer of Information to Stratify NMIBC Patients - Goel, Anshita; Ward, Douglas G.; Gordon, Naheema S.; Abbotts, Ben; Zeegers, Maurice P.; Cheng, K. K.; James, Nicholas D.; Bryan, Richard T.; Arnold, Roland (Frontiers in Oncology, 2020)
Circularized transcript isoforms due to back-splicing are increasingly being reported in different tissues types and pathological states including cancer. Since these circular RNAs (circRNAs) are more stable than linear messenger RNA their identification and profiling in tumor tissue could aid in stratifying patients and may serve as biomarkers. In this study, we have investigated the relationship between circRNA expression and tumor grade in a cohort of 58, mostly non-muscle-invasive bladder cancer patients. From 4571 circRNAs detected, we identified 157 that were significantly differentially expressed between tumor grades relative to the linear transcript. We demonstrated that such grade-related differences can be identified in an independent cohort, and that a large fraction of circRNAs can be, in principle, detected in urine. The differentially expressed circRNAs cluster into subgroups according to their co-expression, subgroups which are enriched for DNA repair, cell cycle and intracellular signaling genes. Since one proposed function of circRNAs is to interfere with gene-regulation by acting as microRNA “sponges,” candidates which were differentially expressed between tumor grades were investigated for potential miRNA target sites. By investigating the circRNAs from bladder cancer related pathways we demonstrated that the expression of these pathways, the circRNAs, and their parental genes are often decoupled and do not correlate, yet that some circRNAs do not follow this tendency. The present study provides the next step for the comprehensive evaluation of this novel class of RNAs in the context of non-muscle-invasive bladder cancer. Intriguingly, despite their possible function as microRNA sponges, they potentially affect host mRNA levels at the transcriptional stage, as compared to post-transcriptional control by miRNAs. Our analysis indicates differences of their activity between bladder cancer tumor stages, and their relative expression levels may provide an additional layer of information for patient stratification.